Improving productive performance of crossbred cattle in cold arid conditions of Kargil through UMMB supplementation - KASHOO, Z A; MEHDI, M; AHMAD, F; AFZAL, Y (The Indian Journal of Animal Sciences, 2014)
The study was carried-out to assess the response of urea molasses mineral block (UMMB) supplementation on milk yield and cost effectiveness with lactating crossbred cows, maintained under smallholder mixed farming system at cold arid conditions, Kargil. Crossbred cows (20) in early to mid lactation were selected; 10 cows were given free access to UMMB in addition to normal ration and the other 10 cows served as control. Supplementation of UMMB licks significantly increased feed intake, milk yield and maintained live weight and body condition score of the cows. UMMB improved general health of the animals with enhanced cash benefit of over ` 41.1/cow/day. The UMMB supplementation technology was found a cost-effective approach to maximize the utilization of locally available feed resources which are scarce in the region as it remains covered with snow and cutoff from rest of world for 6 months.